IMPLEMENTASI PENDIDIKAN AGAMA ISLAM DI SMA MUHAMMADIYAH 2 BOJA: STUDI TENTANG NILAI-NILAI KEISLAMAN DAN PEMBENTUKAN KARAKTER SISWA - Alip Kumaidin; Mukhamad Anieg (As-Sulthan Journal of Education, 2025)
Islamic Religious Education (PAI) has a very vital role in shaping students' character, especially in Muhammadiyah schools which are known for their efforts to integrate Islamic values into every aspect of students' lives. This study aims to analyze the implementation of Islamic Religious Education at SMA Muhammadiyah 2 Boja, with an emphasis on the application of Islamic values and their impact on the formation of students' character. To achieve this goal, this study uses a qualitative approach, with data collection techniques in the form of interviews, observations, and documentation studies. The results of the study indicate that the implementation of PAI at SMA Muhammadiyah 2 Boja does not only focus on teaching religious material alone, but also on forming students' attitudes and behaviors that are in line with Islamic teachings. Values such as honesty, discipline, responsibility, and compassion are integrated thoroughly in this education, which are applied through various activities both inside and outside the classroom.